2022
DOI: 10.1017/s0016756821001394
|View full text |Cite
|
Sign up to set email alerts
|

U–Pb geochronology of Upper Triassic – Lower Jurassic detrital sequences from SE margin of the South China Block: implications for Palaeo-Pacific subduction and tectonic evolution

Abstract: We performed U–Pb dating of detrital zircons and conducted petrological and whole-rock geochemical analyses to assess the provenance of the Upper Triassic – Lower Jurassic clastic rocks in the southeastern margin of the South China Block. Detrital zircon U–Pb ages are mainly classified into age groups of 2000–1700, 900–700, 490–390 and 280–210 Ma, consistent with derivation from the Jiangnan orogenic belt, Nanling Belt, as well as Wuyi and Yunkai domains. Lower Jurassic samples yield a special main age populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 118 publications
1
3
0
Order By: Relevance
“…Consistent with the discovery that the Middle-Late Triassic volcanic rock sequence in the Jinshajiang-Ailaoshan area is covered by a conglomerate unconformity of the Upper Triassic Yongwanshui Formation, the Middle Triassic Lizhigou acidic magmatic F I G U R E 1 4 Geotectonic unit division model of Hainan Island (a) according to Long et al, 2022; according to Tang, 2010; according to Liu et al, 2006; according to Liu, Hu, Chen, et al, 2021;Liu, Hu, et al, 2022. rock in the southern part of Hainan Island is covered by an overlying conglomerate angular unconformity of the Upper Triassic (Gou et al, 2019;He et al, 2020). The detrital zircons obtained by Liu, Hu, Chen, et al (2021) in the southeastern sea area of Hainan Island recorded a metamorphic age of approximately 250 Ma in the Indosinian period, comparable with the high-grade metamorphism of 247-253 Ma in northern Vietnam (Owada et al, 2007) Halpin et al, 2016;Liu, Peng, et al, 2022;Xu, Xia, Lai, Long, & Huang, 2019); (d) southwest margin of the SCB (data from Chai et al, 2022;Duan et al, 2018;Hu et al, 2017;Liu, Peng, et al, 2022;Xu, Xia, Lai, Long, & Huang, 2019;Yang et al, 2012a); (e) southeast margin of the SCB (Hu et al, 2015;Kong, Xu, Tao, et al, 2022;Xu et al, 2018). MDS diagram based on Cross-correlation, Likeness, Kuiper test V value and K-S test D value (e-h), the solid line represents the closest neighbour.…”
Section: Division Of Tectonics and Collision Assembly Mode Of Hainan ...supporting
confidence: 57%
See 2 more Smart Citations
“…Consistent with the discovery that the Middle-Late Triassic volcanic rock sequence in the Jinshajiang-Ailaoshan area is covered by a conglomerate unconformity of the Upper Triassic Yongwanshui Formation, the Middle Triassic Lizhigou acidic magmatic F I G U R E 1 4 Geotectonic unit division model of Hainan Island (a) according to Long et al, 2022; according to Tang, 2010; according to Liu et al, 2006; according to Liu, Hu, Chen, et al, 2021;Liu, Hu, et al, 2022. rock in the southern part of Hainan Island is covered by an overlying conglomerate angular unconformity of the Upper Triassic (Gou et al, 2019;He et al, 2020). The detrital zircons obtained by Liu, Hu, Chen, et al (2021) in the southeastern sea area of Hainan Island recorded a metamorphic age of approximately 250 Ma in the Indosinian period, comparable with the high-grade metamorphism of 247-253 Ma in northern Vietnam (Owada et al, 2007) Halpin et al, 2016;Liu, Peng, et al, 2022;Xu, Xia, Lai, Long, & Huang, 2019); (d) southwest margin of the SCB (data from Chai et al, 2022;Duan et al, 2018;Hu et al, 2017;Liu, Peng, et al, 2022;Xu, Xia, Lai, Long, & Huang, 2019;Yang et al, 2012a); (e) southeast margin of the SCB (Hu et al, 2015;Kong, Xu, Tao, et al, 2022;Xu et al, 2018). MDS diagram based on Cross-correlation, Likeness, Kuiper test V value and K-S test D value (e-h), the solid line represents the closest neighbour.…”
Section: Division Of Tectonics and Collision Assembly Mode Of Hainan ...supporting
confidence: 57%
“…Considering the above question, in this study, the detrital zircon ages of the Middle Triassic strata in central Vietnam (Kham Duc Complex in Kontum Massif, Kenta et al, 2021), west of the Ailaoshan fault (Halpin et al, 2016; Liu, Peng, et al, 2022; Xu, Xia, Lai, Long, & Huang, 2019) and on the southwestern (Chai et al, 2022; Duan et al, 2018; Hu et al, 2017; Liu, Peng, et al, 2022; Xu, Xia, Lai, Long, & Huang, 2019; Yang et al, 2012a) and southeastern margins of the SCB (Hu et al, 2015; Kong, Xu, Tao, et al, 2022; Xu et al, 2018), were collected and compared with those of the Lingwen Formation (Figure 15a–e). In the figures, it can be observed that the detrital zircon age groups in the Triassic strata of Hainan Island, central Vietnam, west of the Ailaoshan fault and the southwestern margin of the SCB all have a strong main peak at approximately 250 Ma, as well as secondary peaks in the range of 500–320 Ma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If not carefully identified as such in the field, these paleocurrent data may lead to erroneous conclusions. Lastly, regional geological data do not support the emergence of an Eastern Plateau as early as Early Jurassic times, as shown by the littoral‐shallow sea deposits in the Upper Triassic‐Lower Jurassic of eastern China (Kong et al., 2022), and paleoaltimetry evidence for the emergence of Eastern Plateau after the Late Cretaceous with paleoelevations >2 km by 100 Ma (Zhang et al., 2016).…”
Section: Discussionmentioning
confidence: 99%